Amorphous CoS nanoparticle/reduced graphene oxide composite as high-performance anode material for sodium-ion batteries. Issue 13 (September 2017) - Zhu, Xiaoming; Jiang, Xiaoyu; Liu, Xiaoling; Xiao, Lifen; Ai, Xinping; Yang, Hanxi; Cao, Yuliang
Abstract: Transition metal sulfides have been proved as promising candidates of anode materials for sodium-ion batteries (SIBs) due to their high sodium storage capacity, low cost and enhanced safety. In this study, the amorphous CoS nanoparticle/reduced graphene oxide (CoS/rGO) composite has been fabricated by a facile one-step electron beam radiation route to in situ decorate amorphous CoS nanoparticle on the rGO nanosheets. Benefiting from the small particle size ( 2 nm), amorphous structure, and electronic conductive rGO nanosheets, the CoS/rGO nanocomposite exhibits high sodium storage capacity (440 mAh g −1 at 100 mA g −1 ), excellent cycling stability (277 mAh g −1 after 100 cycles at 200 mA g −1, 79.6% capacity retention) and high rate capability (149.5 mAh g −1 at 2 A g −1 ). The results provide a facile approach to fabricate promising amorphous and ultrafine metal sulfides for energy storage.